Peran Masyarakat Dalam Meningkatkan Strategi Branding Ekowisata Curug Layung - Zahra, Falia Nur; Prameswari, Aiswara Deswinta; Herdiansyah, Reval Muhammad; Triansyah, Shakila Mi’rajul; Firmansyah, Buyung (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to describe the branding of Curug Layung as an Ecotourism destination that is inspiring, environmentally friendly and has a positive impact. Apart from that, this research also has a positive impact on the economic development of the Curug Layung community and opportunities to improve collective prosperity. The resource persons for this research are the managers and local communities of Curug Layung. This research uses a qualitative descriptive method based on the concept of ecotourism. The data collection techniques used were observation and interviews. The research results indicate that Curug Layung ecotourism has sufficient potential to become a community-based ecotourism that is well managed by the surrounding community in collaboration with the Perhutani institution. This destination offers natural authenticity which is strong branding for Curug Layung so that it can attract tourists to visit.